Electrical Property of 3D Printed Continuous Fiber Reinforced Thermoplastic Composite Mesh Reflecting Surfaces - Kunyang Lin; Xiaofei Ma; Zhen Cui; Youwei Kang; Pengfei Huang; Huanxiao Li; Di Wu; Guanlong Su; Xiaoyong Tian (International Journal of Aerospace Engineering)
Continuous fiber reinforced thermoplastic composites have been widely used in modern aerospace and other high-end manufacturing fields because of their light weight, high strength, fatigue resistance, and corrosion resistance properties. Due to the reinforcement of carbon fiber strands, continuous fiber reinforced thermoplastic composites have good conductivity which makes it a potential material for the preparation of space-borne antennas reflecting surfaces. The reflecting surfaces of common mesh antennas are usually prepared by gold-plated molybdenum wire which is expensive and hard to produce. In this study, the continuous fiber reinforced thermoplastic composites mesh reflecting surfaces are prepared by 3D printing technology. The effect of different mesh shape and mesh size on the electrical properties are investigated systematically. The electrical property of the reflecting surface were tested by waveguide method at the S band with the frequency of 1.9 ~ 2.3GHz. The results show that the reflection loss of the 3D printed continuous fiber reinforced thermoplastic composite mesh reflecting surfaces are lower than 0.25 dB, which can well meet the requirement of space-borne antennas in the S waveband. The reflection loss of the 3D printed continuous fiber reinforced thermoplastic composite mesh reflecting surfaces increases with the increase of mesh size accordingly for both the quadrangular and the triangular mesh reflecting surface. The reflecting property of the mesh reflecting surface tends to be better with a higher surface mass density. The results foresee that the continuous fiber reinforced thermoplastic composites can be used to develop the reflector of large mesh antenna in the future work.